MiR‐422a suppresses SMAD4 protein expression and promotes resistance to muscle loss. Issue 1 (6th October 2017) - Paul, Richard; Lee, Jen; Donaldson, Anna V.; Connolly, Martin; Sharif, Mohammad; Natanek, Samantha Amanda; Rosendahl, Ulrich; Polkey, Michael I.; Griffiths, Mark; Kemp, Paul R.
Abstract: Background: Loss of muscle mass and strength are important sequelae of chronic disease, but the response of individuals is remarkably variable, suggesting important genetic and epigenetic modulators of muscle homeostasis. Such factors are likely to modify the activity of pathways that regulate wasting, but to date, few such factors have been identified. Methods: The effect of miR‐422a on SMAD4 expression and transforming growth factor (TGF)‐β signalling were determined by western blotting and luciferase assay. miRNA expression was determined by qPCR in plasma and muscle biopsy samples from a cross‐sectional study of patients with chronic obstructive pulmonary disease (COPD) and a longitudinal study of patients undergoing aortic surgery, who were subsequently admitted to the intensive care unit (ICU). Results: miR‐422a was identified, by a screen, as a microRNA that was present in the plasma of patients with COPD and negatively associated with muscle strength as well as being readily detectable in the muscle of patients. In vitro, miR‐422a suppressed SMAD4 expression and inhibited TGF‐beta and bone morphogenetic protein‐dependent luciferase activity in muscle cells. In male patients with COPD and those undergoing aortic surgery and on the ICU, a model of ICU‐associated muscle weakness, quadriceps expression of miR‐422a was positively associated with muscle strength (maximal voluntary contraction r  = 0.59, P  < 0.001 and r  = 0.51, P  = 0.004, for COPD and aortic surgery, respectively). Furthermore, pre‐surgery levels of miR‐422a were inversely associated with the amount of muscle that would be lost in the first post‐operative week ( r  = −0.57, P  < 0.001). Conclusions: These data suggest that differences in miR‐422a expression contribute to the susceptibility to muscle wasting associated with chronic and acute disease and that at least part of this activity may be mediated by reduced TGF‐beta signalling in skeletal muscle.